Desmond Tutu’s theology of Forgiveness - Elena Stepanova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
Desmond Tutu, a South African Anglican clergyman and Nobel Peace Prize winner, has made an enormous contribution to the struggle against apartheid. His own position can be defined as a “theology of forgiveness”. The article details the complex intersection of diverse socio-cultural traditions that have influenced Tutu's life stance and theological views, and emphasizes his conviction that Christian theology is always shaped by and exists within a particular socio-historical context. The article identifies two characteristic features of Tutu's theological views: first, is the integration of an African spiritual tradition (Ubuntu) and Anglicanism as a church that initially represented white colonizers but later became active in the struggle against apartheid. Second, is the inseparability of theory and practice, as Tutu's aim was the reconciliation and transformation of both black and white people whose nature had been distorted by racism and apartheid. The article examines the theological foundations of apartheid, namely the influence of the Calvinist doctrine of predestination, and Tutu's teaching of the image of God inherent in all people regardless of differences as a refutation of apartheid. Tutu's work as chairman of the Truth and Reconciliation Commission and his contribution to the transformation of South Africa's social system are highlighted. The article draws the following conclusions: Desmond Tutu's theology of forgiveness is based on the affirmation of the equality of all human beings as created in the image of God; it is impossible to separate theology and politics in his work because for him there was no separation between the religious and the secular.